Accounting from Chinese Entrepreneur Perspectives - Windasari, Ihsanul; Handayati, Puji; Wardoyo, Cipto (AIBPM Publisher, 2020)
This research aims to describe the meaning of accounting on Chinese businessperson perspective. It was conducted at Chinese beekeeping in Malang Regency. Observations, interviews, and documentations were used as data collection technique on this study. This study is qualitative research with phenomenology approach focusing on thought, individual and society as the object of analysis. It was interesting to determine how Chinese entrepreneurs perceive accounting since many entrepreneurs believe Chinese entrepreneurs can be relied on. This study contended that Chinese entrepreneurs see accounting as (1) information; (2) calculation (decision based); and (3) accountability.